The space technology to solving societal issues in Bolivia: An overview - Vargas Cuentas, Natalia (2017)
Aerospace development for a country represents their technological level, development capacity, and their sovereignty. The development of the aerospace industry brings technology that the society use in the daily lives. The technology initially developed to explore the universe is the same that today we use in our daily lives. Today we can see that the South American countries, including Bolivia, are showing strong economic growth, and this leads to a higher rate of development and increased investment in new technologies. For example in recent years, it has seen as many governments in South America, have decided to invest in space systems. These space systems have different applications, among them we can mention, remote sensing technology for disaster management, urban planning improvement, environmental assessment, telecommunications systems. In the space technology field, Bolivia is developing its expertise with the creation of the Bolivian Space Agency (ABE), the launch of its first telecommunications satellite Túpac Katari (TKSat-1), the training of Bolivian professionals, and the creation of two ground stations. Other important thing is that the Bolivian Space Agency announced the country's willingness to purchase another satellite soon. In that context, the present research wants to show how our communication satellite has opened a great opportunity for our rural communities through the integration into their life new technologies of information and communication. Because, thanks to our satellite, over 1000 telecentres were installed in remote rural communities that never had direct access to telecommunications services. In these telecentres, thousands of Bolivians have, for the first time, the possibility of connecting to the world and somehow reduce the difference gap between the rural area and the urban area. The country knows that in this new era, we must move from being a country that dependent from others, to become a country applying the learned concepts. It is necessary to become a country with the capacity to do research activities and to be able to develop its technology because it has the human resource to meet this challenge and we need to offer a chance to inspire people and bring to their attention the potential and benefits of the space sector.